2013
DOI: 10.1007/s00705-013-1828-y
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of neutralising antibodies to chimpanzee adenovirus type 6 and type 7 in healthy adult volunteers, patients with chronic hepatitis B and patients with primary hepatocellular carcinoma in China

Abstract: The presence of neutralising antibodies (NAbs) against adenovirus in the population is a major hurdle preventing the effective use of replication-defective adenoviruses (Ads) as candidates for gene therapy and vaccine vectors for many diseases. Only a few studies have described the epidemiology of pre-existing immunity to chimpanzee Ads in China. To assess the prevalence of NAbs to chimpanzee adenovirus serotypes 6 and 7 (AdC6 and AdC7), we enrolled 998 healthy participants from five regions in China as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…HAdV-C2 global seroprevalence is relatively high (36-92%) and ≥ HAdV-C5 [120,121]. HAdV-C6 was presented as a low prevalence type by one study in the United States (8.5% adult and 2% children [122] and reach 12% in of healthy adult in China [123]), while others studies show a seroprevalence rate fluctuating between 78% in Thailand and Cameroon; 73% in South Africa and 71% in Malawi [124].…”
Section: Moving Forwardmentioning
confidence: 96%
“…HAdV-C2 global seroprevalence is relatively high (36-92%) and ≥ HAdV-C5 [120,121]. HAdV-C6 was presented as a low prevalence type by one study in the United States (8.5% adult and 2% children [122] and reach 12% in of healthy adult in China [123]), while others studies show a seroprevalence rate fluctuating between 78% in Thailand and Cameroon; 73% in South Africa and 71% in Malawi [124].…”
Section: Moving Forwardmentioning
confidence: 96%
“…The frequency of nAbs against ChAd6 are similar in these populations except in Africa where it peaks below 40%. 14,46,62 Furthermore, unlike rare human Ad serotypes, ChAd have demonstrated great efficacy in pre-clinical studies including ChAd7 in a mouse model of EBOV infection, 63 ChAd68 (SAd-24) in a NHP model of rabies, 64,65 ChAd63, ChAd7 or ChAd9 in combination with modified vaccinia Ankara (MVA) boost in a malaria mouse model, 66,67 and ChAdOx1 in a rodent model of Rift Valley Fever (RVF). 68 In addition, in Phase I clinical trials against Malaria and HCV, ChAd63 46 and ChAd3, 69 respectively, were found to be safe and able to generate robust, broad and polyfunctional T cell responses against the transgene.…”
Section: Ad Vectors Based On Alternative Adenovirusesmentioning
confidence: 99%
“…The majority of these adenovirus vectors are from species B, C, D, and E. Adenovirus vectors from avian, bovine, and other species have also been constructed, but their different genomic structures may necessitate the development of a novel manufacturing platform for clinical development (17,18). Old World monkey adenoviruses have been hypothesized to be distinct from both human and chimpanzee adenoviruses and may offer unique advantages, such as the ability to more efficiently bypass preexisting immunity to human adenoviruses (12,(19)(20)(21)(22)(23)(24), while maintaining the genomic structure and growth properties of human adenoviruses.…”
mentioning
confidence: 99%